Freshwater fish diversity hotspots for conservation priorities in the Amazon Basin - J?z?quel, C?line; Tedesco, Pablo A.; Darwall, William Robert Thomas; Dias, Murilo Sversut; Frederico, Renata Guimarães; Hidalgo, Max H.; Hugueny, Bernard; Maldonado-Ocampo, Javier Alejandro; Martens, Koen M.; Ortega, Hernán; Torrente-Vilara, Gislene; Zuanon, Jansen; et al. (Conservation Biology, 2020)
Conserving freshwater habitats and their biodiversity in the Amazon Basin is a growing challenge in the face of rapid anthropogenic changes. We used the most comprehensive fish-occurrence database available (2355 valid species; 21,248 sampling points) and 3 ecological criteria (irreplaceability, representativeness, and vulnerability) to identify biodiversity hotspots based on 6 conservation templates (3 proactive, 1 reactive, 1 representative, and 1 balanced) to provide a set of alternative planning solutions for freshwater fish protection in the Amazon Basin. We identified empirically for each template the 17% of sub-basins that should be conserved and performed a prioritization analysis by identifying current and future (2050) threats (i.e., degree of deforestation and habitat fragmentation by dams). Two of our 3 proactive templates had around 65% of their surface covered by protected areas; high levels of irreplaceability (60% of endemics) and representativeness (71% of the Amazonian fish fauna); and low current and future vulnerability. These 2 templates, then, seemed more robust for conservation prioritization. The future of the selected sub-basins in these 2 proactive templates is not immediately threatened by human activities, and these sub-basins host the largest part of Amazonian biodiversity. They could easily be conserved if no additional threats occur between now and 2050. © 2020 Society for Conservation Biology